The Sediment Profile and Heavy Metal Content of Lead (Pb), Copper (Cu), and Silver (Ag) in The Waters of Saparua Island - Anakotta, Jaicson G.; Male, Yusthinus T.; Sekewael, Serly J.; Gaspersz, Nelson (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
This study determined the distribution levels of heavy metals Pb, Cu, and Ag in sediments in the waters of Saparua Island. It characterized the sediments in the seas of Saparua Island. Parameters are physical and chemical parameters of waters, determination of total organic carbon (TOC), and digestion of sediment samples for SSA testing. The results obtained levels of copper metal contained in the sediments from 0.1583–1.9531 mg/L and <4–78 ppm. The level of lead metal contained in the sediments in the waters of Saparua Island ranges from <12–26 ppm. Metal oxides, especially metal oxides formed from Cu, were found in sediments in the waters of Saparua Island with location points P.8 and P.9, namely CuO 0.0056% and 0.0031% and in sediments in Saparua Island waters with a value of 2Ɵ in sediment samples. P.2, P.3, P.6, P.8, P.9, and P.11 have the highest intensity which is the characterization of metal oxide 2Ɵ= 27.7464°, 29.4759, 26.2979, 26.6686, 26.7007, and 24.3695 indicate the presence of CaO (calcium oxide) phases at points P.2, P.3, and P.6. the SiO2 (silica) phase which is the most abundant metal in sediment samples P.8, P.9, and P.11 based on the XRF test.